Evaluasi Efektivitas HRIS dengan Metode TAM 3 untuk Mendukung Kinerja Administrasi Kepegawaian PT Minarta Dutahutama - Reyhan, Andre; Achyani, Yuni Eka (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2025)
PT Minarta Dutahutama is a national-scale company engaged in architectural and construction services. Since 2022, the company has implemented a web-based Human Resource Information System (HRIS) that integrates essential modules, including employee data, attendance, leave, performance evaluation, and HR reports. This study aims to evaluate the effectiveness of the HRIS in supporting personnel administration performance at PT Minarta Dutahutama using the Technology Acceptance Model 3 (TAM 3) framework. The system is expected to enhance operational efficiency, ensure accuracy in data management, and accelerate decision-making. The research applies a descriptive qualitative approach, with data collected through questionnaires, semi-structured interviews, and direct observation. The sample involved five active HRIS users selected by total sampling due to the small population. Evaluation was carried out on six constructs of TAM 3: perceived usefulness, perceived ease of use, output quality, subjective norm, computer anxiety, and behavioral intention to use. The findings indicate that HRIS is highly useful, easy to operate, produces good output quality, and is supported by a positive work environment. The study concludes that HRIS is effective in strengthening personnel administration processes, with recommendations for improved training and continuous system development to optimize user adaptation.